Theodizee als biblisch erzählte Geschichte Theodizee als biblisch erzählte Geschichte - Kaiser, Gerhard (Zeitschrift für Theologie und Kirche, 2005)
In the opinion of J. B. Metz, the theodicy question was the central theme of biblical theology which is a result of the temporality of God's actions. According to the theory expressed in this article, biblical narration, which creates a temporal meaning for our life, corresponds to this. This is expressed most vividly in the narration of critical situations which lead to fulfilment rather than to a logical solution.